The Politics of International Labour Migration and Globalisation in Africa - Carciotto, Sergio (New Agenda: SA Journal of Social and Economic Policy, 2024)
This article examines the intricate relationship between migration, globalisation and socio-economic dynamics in Africa. It highlights the prevalence of intra-African migration, characterised by short-distance movements primarily driven by economic factors. The study critiques the dominant narrative framing migration as a purely developmental tool, arguing that the benefits of remittances and diaspora investments are often overshadowed by structural inequalities and the precarious conditions faced by migrant workers. The  article also explores the role of states and international organisations in shaping migration policies, revealing a tension between the aspirations for regional integration and the realities of restrictive immigration practices. Ultimately, it calls for a nuanced  understanding of migration that prioritises the rights of migrant workers and advocates for comprehensive governance frameworks to address exploitation and uphold human rights. This reflection contributes to the discourse on migration governance, highlighting the need for a collaborative approach that involves both state and non-state actors to effectively navigate the complexities of migration in the context of globalisation.